If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=-4(g+18)
We move all terms to the left:
-12-(-4(g+18))=0
We calculate terms in parentheses: -(-4(g+18)), so:We get rid of parentheses
-4(g+18)
We multiply parentheses
-4g-72
Back to the equation:
-(-4g-72)
4g+72-12=0
We add all the numbers together, and all the variables
4g+60=0
We move all terms containing g to the left, all other terms to the right
4g=-60
g=-60/4
g=-15
| x+99+x+70+97=360 | | 2(k+-1)=-14 | | 14=-2(q+-12) | | x+64+x+82+53+63=360 | | 16=4(h-13) | | x+99+x+57+x+69=360 | | g+65.75=59.25 | | 3(z-15)=15 | | 6x+6.51=51.25 | | 30+f=180 | | 16-4x+7+1=-16 | | t=80+10 | | b+30=180 | | a/18=6 | | 4(x-2+10)=-116 | | 3=-16t^2+36 | | 155=-20x-5 | | 125=18x-2 | | 4.50=100x | | 10d=10d+6 | | 20=17-x | | -4q-7=-7-4q | | (7/22)44=2r | | 58-3x=46 | | 414=1.15x | | 3x/2-8/1=x-4/6 | | 414=0.15x | | -2x+8=-5x+23 | | -2x+8=-5+23 | | 5a=2a=32 | | 10=n-4/5 | | 25x=1030 |